Poor mental health of livestock farmers in Africa: a mixed methods case study from Ghana - Nuvey, Francis Sena; Kreppel, Katharina; Nortey, Priscilla Awo; Addo-Lartey, Adolphina; Sarfo, Bismark; Fokou, Gilbert; Ameme, Donne Kofi; Kenu, Ernest; Sackey, Samuel; Addo, Kennedy Kwasi; Afari, Edwin; Chibanda, Dixon; et al. (BMC public health, 2020)
Background Agriculture represents the mainstay of African economies and livestock products are essential to the human population’s nutritional needs. However, in many developing countries, including Ghana, livestock production fails to meet demand due to population growth and negative effects of climate change. One of the challenges to production is livestock loss affecting farmers. However, despite stressful events experienced, livestock farmers’ mental health is poorly documented. This study aims to identify the root causes of livestock losses and their influence on pastoralists’ mental health. Methods We conducted a mixed methods study in two districts in the Northern and Southern Belts of Ghana. Using the Depression Anxiety and Stress Scale–21 and guided interviews, we collected quantitative and qualitative data from 287 livestock farmers and 24 key-informants respectively. Mental health scores were categorized using standard guidelines. We evaluated the factors that explained variations in mental wellbeing using general linear models ( α = 0.05). Results About 85% (240/287) of the livestock farmers lost cattle within 1 year. Of these, 91% lost cattle to animal diseases, 50% to theft and 27% to pasture shortages. Qualitative findings reveal that due to poor access to veterinary services, farmers treat livestock diseases themselves with drugs from unregulated sources and often sell diseased cows for meat to recover losses. Findings showed that 60% of livestock farmers had poor mental health. Of those, 72% were depressed, 66% anxious and 59% stressed. Mental wellbeing was negatively associated with the number of adverse events experienced, proportion of livestock lost to most of the major loss factors, emotional attachment to livestock and self-reported physical illnesses in farmers, but positively associated with increasing herd size [F (8,278) = 14.18, p < 0.001, R 2 = 0.29]. Conclusions Livestock diseases are the leading cause of losses to livestock farmers, whose mental wellbeing is negatively affected by these losses. Although an adaptive strategy by farmers to compensate for poor veterinary services, the arbitrary use of veterinary drugs and sale of diseased cattle pose health risks to the public. Further research to evaluate the performance of veterinary services in Ghana, mental health problems and risk to human health due to potential high-risk meat entering the food chain, is needed.